The aesthetics of configuration systems and their applications In women's textile designs (the marine environment as a model) (Journal of the College of Basic Education, 2022)
The textile industry is a product of human civilization, and it is a measure of the sophistication and development of nations, and their prosperity is linked to the prosperity of the societies in which they thrive. The aesthetic perspective and the type of formative systems used on fabrics and the methods it creates to rearrange the forms of design in order to achieve the aesthetic and expressive aspects and in line with the function